Pediatric sublingual dermoid and epidermoid cysts: A 20-year institutional review. (November 2020) - Misch, Emily; Kashiwazaki, Ryota; Lovell, Mark A.; Herrmann, Brian W.
Abstract: Introduction: Pediatric cystic sublingual masses often present a diagnostic dilemma for practitioners. Though uncommon, dermoid or epidermoid cysts can present in the sublingual space at any age and are often misdiagnosed as an inflammatory pseudocyst (ranula) or lymphatic malformation. Imaging may not always identify the underlying etiology, requiring physicians to maintain a high index of suspicion for these relatively rare oral cysts. Objectives: To describe the presentation and treatment of sublingual dermoid and epidermoid cysts presenting to a tertiary children's hospital over 20 years. Methods: A retrospective review of all pathology specimens identified as dermoid or epidermoid cysts within the sublingual space from 1999 to 2019. Patient charts were then reviewed for relevant clinical, imaging, and operative data. Results: Twelve pediatric patients were identified (8 female, 4 male) with a mean age of 7.2 years (SD 5.6). Eighty six percent (6/7) of dermoid cysts were found in female patients, while 60% (3/5) of epidermoid cysts were in male patients. Multiple dermoid and epidermoid cysts were each found in one patient (8%). Two epidermoid cysts presented in the neonatal period. Preoperative diagnosis included nondiagnostic "cystic mass" (33%), ranula (25%), lymphatic malformation (LM) (17%), and dermoid/epidermoid cyst (17%). Two thirds of patients (8/12) underwent imaging, with all receiving either MRI or CT. Although MRI was the most likely to suggest the possibility of a dermoid/epidermoid cyst (2/4), ranula was the most common primary radiographic diagnosis (5/8). One patient underwent sclerotherapy for presumed LM one year prior to surgical excision of the cyst. Eleven patients (92%) underwent intraoral excision, one (8.3%) underwent a combined intraoral/extraoral approach. Conclusions: To our knowledge, this review represents the largest case series of pediatric sublingual dermoid and epidermoid cysts to date. This series contained higher levels of epidermoid cysts and female patients than previously reported in the literature. Identifying more dermoid cysts in females and epidermoid cysts in males is also a new finding. MRI was superior to CT and US regarding the presence of a dermoid/epidermoid cyst. Frequently misdiagnosed, it is important to consider these relatively rare pathologies when treating children presenting with sublingual masses in order to avoid delayed and/or inappropriate treatment.